TESTING TRADE-OFF THEORY IN CORPORATE FINANCIAL DISTRESS: A RANDOM EFFECTS PANEL APPROACH - Nanda Putra Saragi; Nardo Tedrick (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
Drawing on Trade-Off Theory, this study examines corporate financial distress in an emerging economy by examining how firms balance the tax benefits of debt against the costs of distress. It analyses the effects of leverage, liquidity, institutional ownership, while assessing whether operational efficiency moderates these relationships. The sample comprises 153 firms listed on the Indonesia Stock Exchange over 2023–2024, generating 306 firm-year observations from S&P Capital IQ. Panel regression analysis was conducted using Chow, Lagrange-Multiplier, Hausman tests, with the Random Effects model selected as the preferred estimator. The findings show that leverage and liquidity significantly influence financial distress, supporting the risk–return trade-off in capital structure decisions. However, institutional ownership has no significant direct effect, operational efficiency does not moderate relationships. Overall, the results highlight the importance of prudent capital structure and liquidity management and provide evidence of the relevance of Trade-Off Theory in an emerging market context.